Implementation of Visual Learning Media to Improve Early Childhood Fine Motor in Tk PGRI Among Siwi, Adipuro Village, Kaliangkrik - Wahyu Trinugroho Wahyu; Siswanto; Laili Syarifah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Fine motor skills play a crucial role in early childhood development, involving coordination between eyes and hands. This article explores the significance of early childhood education in nurturing these skills, particularly focusing on kindergarten-aged children. Drawing on various studies and educational theories, it emphasizes the importance of providing adequate stimulation and learning opportunities during the formative years of 0-6. The research highlights the need for innovative approaches in teaching methods, especially considering the tendency of young children to become easily bored. Utilizing the Asset-Based Community Development (ABCD) method, the study conducted community service activities aimed at enhancing fine motor skills in early childhood within a specific village. Through observation, interviews, and collaboration with teachers, the research identified weaknesses in fine motor skills among children and developed visual learning media to address these issues. The study implemented various activities such as puzzles, coloring, and crafting, which proved to be engaging and effective in improving children's motor skills. Additionally, it discusses the theoretical framework of cognitive development, particularly Piaget's stages, emphasizing the role of play and hands-on experiences in facilitating learning. Ultimately, the article underscores the importance of utilizing available resources and integrating innovative learning media to create enjoyable and effective learning experiences for young children, thereby promoting their holistic development.